Giant kelp vegetative propagation: Adventitious holdfast elements rejuvenate senescent individuals of the Macrocystis pyrifera "integrifolia" ecomorph. Issue 1 (3rd January 2017) - Murúa, Pedro; Müller, Dieter G.; Patiño, David J.; Westermeier, Renato
Abstract : Recent findings on holdfast development in the giant kelp highlighted its key importance for Macrocystis vegetative propagation. We report here for the first time the development of adventitious holdfasts from Macrocystis stipes. Swellings emerge spontaneously from different areas of the stipes, especially in senescent or creeping individuals. After being manually fastened to solid substrata, these swellings elongated into haptera, which became strongly attached after 1 month. Within 4 months, new thalli increased in size and vitality, and developed reproductive fronds. Our results suggest the usage of these structures for auxiliary attachment techniques. These could act as a backup, when primary holdfasts are weak, and thus improve the survival rate of the giant kelp in natural beds.